Gastrointestinal tract in children with novel coronavirus infection and post-COVID-19 syndrome. The role of synbiotics for improving clinical symptoms, gut microbiota, and intestinal permeability - V.P. Novikova; A.V. Polunina; S.L. Bannova; V.V. Dudurich; L.G. Danilov; A.E. Blinov; O.N. Varlamova (LCC «Medicine-Inform», 2023)
V.P. Novikova1, A.V. Polunina1, S.L. Bannova1, A.L. Balashov1,2, V.V. Dudurich3, L.G. Danilov3, A.E. Blinov1, O.N. Varlamova1 1St. Petersburg State Pediatric Medical University, St. Petersburg, Russian Federation 2City Polyclinics No. 56, St. Petersburg, Russian Federation 3CerbaLab Ltd, St. Petersburg, Russian Federation Background: studying the consequences of novel coronavirus infection is currently relevant. Many observations demonstrate that SARS-CoV-2 affects the gastrointestinal tract, gut microbiota composition, and intestinal permeability. Aim: to assess whether Maxilac® Baby synbiotic effects qualitative and quantitative composition of gut microbiota and intestinal permeability in children aged 3-14 with mild-to-moderate COVID-19. Patients and Methods: an open, observational, prospective, single-center study with minimal intervention was conducted. Group 1 included 16 children who received Maxilac® Baby 4 weeks after recovery. Group 2 children did not receive synbiotics after recovery. History and complaints were assessed, gut microbiome composition was determined, and fecal zonulin was measured at disease onset, time of recovery (day 14), and 4 weeks after recovery. Results: at disease onset, abdominal pain and diarrhea were reported in 16 children (50%), nausea in 8 children (25%), and vomiting in 1 child (3.1%). At the time of recovery, only abdominal pain was reported in both groups (4 patients each). Thirty days after recovery, re-appearance of intestinal symptoms was reported in group 2. No significant differences in the microbiome diversity profile at birth level were revealed between children with the COVID-19 at onset and healthy age-matched children. Taxa (species) whose predominance was typical for each group were identified. Conclusions: post-COVID-19 syndrome in children aged 3-14 diagnosed with mild-to-moderate disease who received Maxilac® Baby for 1 month after recovery is characterized by the lack of nausea, vomiting, and diarrhea, less abdominal pain, no changes in fecal zonulin levels, and biodiversity of gut microbiome, including those assessed by Shannon diversity index. Keywords: SARS-CoV-2, COVID-19, intestinal permeability, gut microbiome, 16s rRNA sequencing, zonulin, novel coronavirus infection, post-COVID-19 syndrome. For citation: Novikova V.P., Polunina A.V., Bannova S.L., Balashov A.L., Dudurich V.V., Danilov L.G., Blinov A.E., Varlamova O.N. Gastrointestinal tract in children with novel coronavirus infection and post-COVID-19 syndrome. The role of synbiotics for improving clinical symptoms, gut microbiota, and intestinal permeability. Russian Journal of Woman and Child Health. 2023;6(3):283-289 (in Russ.). DOI: 10.32364/2618-8430-2023-6-3-10.